Pengujian Performa Website SMA Muhammadiyah 4 Yogyakarta Menggunakan K6 Tools dan GTMetrix - Muhammad Rizky; M. Fahrul A; Agfa Oktaviana; Masbina Ajeng Lestari (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2022)
The use of the website in schools is very important considering the needs of students to access information in order to add information. this requires fast and stable performance that can be accessed by all users of the website, therefore the performance of the website at SMA Muhammadiyah 4 Yogyakarta should be a point of attention because it plays an important role in supporting various information. GTmetrix software is one of the tools made by Google which is designed to determine website performance, it can provide information about parts of the website that have poor values ??and provide recommendations for things that need to be improved. Whereas K6 is an open source load testing tool to test the performance of APIs, microservices and websites. Based on the results of website testing using GTMetrix at SMA Muhammadiyah 4 Yogyakarta, it was obtained an average Performance with a score of 53% or grade E. and an average Structure with a score of 58%. Measurements using K6 Tools resulted in a response time of 2991 milliseconds, after that with 6322 requests with 23 average failures and an average request of 19 requests/second.